INTERNAL RISK FACTORS IN CREDIT DISTRIBUTION - Silaban, Pasaman; Silaban, Frederick Saroha; Sihombing, Eriko (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
Rural Banks in North Sumatra Province during the 2017-2021 period experienced an increase in the amount of credit disbursed to the public, but it was not significant, where there were microeconomic factors that influenced the increase in the amount of credit, such as decreasing CAR, increasing NPL and decreasing LDR value will affect BPR's ability to maximize the amount of funds to distribute credit in the future even though third party funds increase during 2017-2021. This research aims to find out what internal risk variables are, namely variables CAR, third party funds, NPL, LDR directly, partially or simultaneously influence the amount of credit that will be distributed by BPRs in North Sumatra Province. This research uses quantitative research methods using panel data regression analysis using the eviews application, where the data used is secondary data originating from the financial reports of 53 BPRs in North Sumatra Province, where this data is collected from microeconomic aspects such as Capital Adequacy Ratio (CAR), Third Party Funds (DPK), Non Performing Loans (NPL), and Loan to Deposit Ratio (LDR).